The Effect of Education on Health: Evidence from National Compulsory Schooling Reforms - Raquel Fonseca; Pierre-Carl Michaud; Yuhui Zheng (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2018)
This paper sheds light on the causal relationship between education and health outcomes. We combine three surveys (SHARE, HRS and ELSA) that include nationally representative samples of people aged 50 and over from fifteen OECD countries. We use variation in the timing of educational reforms across these countries as an instrument for education. Using IV-Probit models, we find causal evidence that more years of education lead to a lower probability of reporting poor health, less likely of having limitations in functional status (ADL and iADLs), and lower prevalence for diabetes. These effects are larger than those from the Probit that do not control for the endogeneity of education. The relationship between education and cancer is positive in both Probit and IV-Probit models. The causal impacts of education on other chronic conditions as well as functional status are not established using IV-Probit models.
Keywords: 330